UPAYA MENINGKATKAN KETERAMPILAN BERBICARA DAN MOTIVASI BELAJAR PESERTA DIDIK DENGAN STRATEGI SOSIODRAMA PADA MUATAN BAHASA INDONESIA KELAS VI MI MA’ARIF KLANGON TAHUN PELAJARAN 2021/2022 - Juni Arifin Hidayat (Pedir Research Institut, 2022)
Abstract:. This study aims to determine the speaking skills and learning motivation of students by applying sociodrama strategies. The research was carried out in class VI of MI Ma'arif Klangon, Salam District, Magelang Regency, Central Java Province, with details of the research subjects of 8 students of class VI MI Ma'arif Klangon. Consisting of 2 male students and 6 female students this was carried out in 3 cycles, where each cycle was carried out 1 time for 1 week. Researchers used the methods of observation, interviews, documentation, and questionnaires in collecting data. The instruments used were observation sheets, student questionnaires, and interview instruments. The results showed that through the implementation of sociodrama strategies in Indonesian language lessons, students' speaking skills improved. The percentage of students' speaking skills increased both in cycle I to cycle II and cycle II to cycle III. The speaking skill of students before the implementation of the cycle action is still very low. After taking action in the first cycle, the percentage of students' speaking skills was 38.32% with sufficient criteria. The second cycle experienced an increase in speaking skills, namely to 55.83% with sufficient criteria. Meanwhile, in the third cycle there was an increase compared to the first and second cycles to 74.16% with good criteria. Through the application of sociodrama strategies in Indonesian language lessons, students' learning motivation has increased. The success of students' learning motivation has increased by reaching a percentage of 90.20% with good criteria. That means that the application of sociodrama strategies in Indonesian language lessons can increase students' learning motivation by 6.87%. The percentage in the first cycle was 77.70%, in the second cycle it reached 83.33%, while in the third cycle it reached 90.20% with good criteria.